Calidad de servicio y satisfacción de los clientes del banco Ripley Perú S.A. - Agencia Mall Aventura Plaza, Trujillo, año 2011. - Garcia Garrido, Liz Caro (2011)
is currently some unanimity that attribute that contributes primarily to determine the position of the company in the long run is the opinion of the customers about the product or service to receive. It is obvious that, to enable customers to form an opinion positive, company must amply satisfy all your needs and expectations. This is what has been called quality of service. Therefore, if satisfy the expectations of the customer is as important as it has been said, it is then necessary to have adequate information on the client that contains aspects related to their needs, with the attributes that are set to determine the level of quality achieved. Quality, and more specifically the quality of the service, is becoming a prerequisite today to compete in organizations around the world, that implications into account results in the short and the long term, are very positive for companies involved in such processes. In this way, the quality of the service becomes a strategic element to confer a distinctive and lasting advantage in time to those that try to reach it. This research aims to meet quality of service factors influencing the satisfaction of the customers who use services of Banco Ripley S.A., agency Mall Aventura Plaza - Trujillo. This took place a survey to customers to carry out financial operations the Bank, taking a sample of a population of 30848 210 customers. The results can be said that the quality of the service influences in a satisfactory manner the satisfaction of the clients of Banco Ripley.